Prediction of Second Melting Temperatures Already Observed in Pure Elements by Molecular Dynamics Simulations - Robert F. Tournier (MDPI AG, 2021)
A second melting temperature occurs at a temperature Tn+ higher than Tm in glass-forming melts after heating them from their glassy state. The melting entropy is reduced or increased depending on the thermal history and on the presence of antibonds or bonds up to Tn+. Recent MD simulations show full melting at Tn+ = 1.119Tm for Zr, 1.126Tm for Ag, 1.219Tm for Fe and 1.354Tm for Cu. The non-classical homogeneous nucleation model applied to liquid elements is based on the increase of the Lindemann coefficient with the heating rate. The glass transition at Tg and the nucleation temperatures TnG of glacial phases are successfully predicted below and above Tm. The glass transition temperature Tg increases with the heating rate up to Tn+. Melting and crystallization of glacial phases occur with entropy and enthalpy reductions. A universal law relating Tn+ and TnG around Tm shows that TnG cannot be higher than 1.293Tm for Tn+= 1.47Tm. The enthalpies and entropies of glacial phases have singular values, corresponding to the increase of percolation thresholds with Tg and TnG above the Scher and Zallen invariant at various heating and cooling rates. The G-phases are metastable up to Tn+ because the antibonds are broken by homogeneous nucleation of bonds.